2014
DOI: 10.1111/jgs.12993
|View full text |Cite
|
Sign up to set email alerts
|

Intervention with the Screening Tool of Older Persons Potentially Inappropriate Prescriptions/Screening Tool to Alert Doctors to Right Treatment Criteria in Elderly Residents of a Chronic Geriatric Facility: A Randomized Clinical Trial

Abstract: Implementation of STOPP/START criteria reduced the number of medications, falls, and costs in a geriatric facility. Their incorporation in those and similar settings is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
278
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(290 citation statements)
references
References 29 publications
7
278
1
4
Order By: Relevance
“…Thirteen trials (4226 participants) in care facilities studied multifactorial interventions (Beck 2016; Becker 2003; Dyer 2004; Jensen 2002; Kerse 2004; McMurdo 2000; Neyens 2009; Ray 1997; Rubenstein 1990; Salvà 2016; Shaw 2003; Walker 2015; Whitney 2017). Eleven trials were cluster-randomised trials (Beck 2016; Becker 2003; Dyer 2004; Jensen 2002; Kerse 2004; McMurdo 2000; Neyens 2009; Ray 1997; Salvà 2016; Walker 2015; Whitney 2017; 3470 participants), and two were individually randomised (Rubenstein 1990; Shaw 2003; 756 participants).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen trials (4226 participants) in care facilities studied multifactorial interventions (Beck 2016; Becker 2003; Dyer 2004; Jensen 2002; Kerse 2004; McMurdo 2000; Neyens 2009; Ray 1997; Rubenstein 1990; Salvà 2016; Shaw 2003; Walker 2015; Whitney 2017). Eleven trials were cluster-randomised trials (Beck 2016; Becker 2003; Dyer 2004; Jensen 2002; Kerse 2004; McMurdo 2000; Neyens 2009; Ray 1997; Salvà 2016; Walker 2015; Whitney 2017; 3470 participants), and two were individually randomised (Rubenstein 1990; Shaw 2003; 756 participants).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not report data suitable for use in the quantitative analysis (Beck 2016; Ray 1997). Three studies (2160 participants) reported data on hip fractures (Becker 2003; Jensen 2002; Shaw 2003), and one reported total fractures (Salvà 2016). Three studies (312 participants) reported adverse-event data (Beck 2016; McMurdo 2000; Whitney 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent RCT, the use of the STOPP and START (Screening Tool to Alert doctors to Right Treatment) criteria as intervention guidelines had been shown significantly to reduce the number of medications and falls at a chronic care geriatric facility. In addition, the intervention contributed to a saving of US$29 for every patient monthly [6]. Nevertheless, one particularly important aspect of all available criteria for PIMs is that they only list ''potentially'' inappropriate medications.…”
Section: Main Textmentioning
confidence: 98%
“…Although the exact scope of potentially inappropriate medications (PIMs) may differ between these published criteria, PIMs in older people are generally referred to as medications that lack evidence-based indications, medications with treatment risks that may outweigh their benefits, medications that are significantly associated with ADRs, and those that are likely to interact with other medications or diseases [3]. The literature includes many studies pertaining to the use of PIMs among older people and the use of PIMs has been reported to be prevalent in up to 79 % of older people, depending on the type of criteria used, study settings and countries [4][5][6][7][8].…”
Section: Main Textmentioning
confidence: 98%
“…Use of the tool enables the identification of avoidable adverse events and improvement in a range of outcomes. [17][18][19] Hence the NICE guideline on medicines optimisation advocates using the STOPP/START tool to identify patients who should be targeted for medication reviews.…”
Section: Identifying Patients Who May Benefit From Deprescribingmentioning
confidence: 99%